Pernikahan Usia Dini di Kota Serang - Hidayah, Septi; Bilbina, Zahwa Aurelia; Nabil, Muhammad Akfar; Fasha, Salwa Rizkiya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
In a marriage which is a very important thing because it is the union of two people who will complement each other, maintain and perfect religion, in the current phenomenon that exists in society, the large number of marriages at an early age is a factor that is the reason for distancing themselves from the phenomenon. The woman becomes pregnant out of wedlock which would violate religious and social norms. As for other factors to reduce the burden of responsibility from parents on children, couples who marry young generally have a high tolerance for change and mature more quickly for those involved in young marriages. This article was created with the aim of finding out the phenomenon of young marriage in Serang City, Banten Province. This research used literacy study methods, data collection techniques for researchers using interviews, observation and literature study. The results of the research that researchers can carry out are. (1) Factors that encourage young people to marry in Serang City (2) What strategies are used when there is conflict in marriage (3) How do teenagers in Serang City carry out their daily lives in the role of head of the family and housewife.